KESUBURAN TANAH DAN LAJU FOTOSINTESIS TANAMAN KELAPA SAWIT YANG MENUNJUKKAN GEJALA WHITE STRIPE PADA LAHAN GAMBUT DI LABUHAN BATU - Edy Sigit Sutarta; Muhdan Syarovy (Pusat Penelitian Kelapa Sawit, 2019)
White stripe is the loss of green pigment with elongated shape on left and right side of the mid-rib. White stripe is often associated with an imbalance in the N/K nutrient ratio in oil palm. This study aims to determine soil fertility, growth, and photosynthesis rate of oil palm that expressing white stripe symptoms on Fluvaquentic Haplosaprists in Labuhan Batu, North Sumatra. This research was conducted by observing the ecophysiology of 3 plant conditions consisting of a) healthy oil palms, b) oil palms expressing white stripe symptoms, and c) oil palms expressing Boron deficiency symptoms. The results showed that peat soil at the research site has good fertility status. Soil fertility of all treatments are similar except its available nutrients, where the oil palms expressing white stripe symptoms have average P available, K, Ca, Na, and Mg exchanged lower than healthy oil palms as well as oil palms expressing Boron deficiency symptoms. Oil palms expressing white stripe symptoms have low leaf N/K rasio (2.19), and have no relation with Boron deficiency, with unsignificant leaf area indeks (LAI) compared to other treatments. Low chlorophyll content of oil palms expressing white stripe and Boron deficiency symptoms have affected to low rate of photosynthetic rate and, If not corrected immediately, white stripe and also boron deficiency will affect to oil palm growth and productivity.